The Information Seeking Behavior of Digital Native and Digital Immigrant Students of Bogor Agricultural University - Janti Gristinawati Sujana; Pudji Muljono; Djuara P. Lubis; Sulistyo Basuki (Journal of Education and Learning (EduLearn), 2018)
Technological expansion and the changing way individuals gain access to information has deeply impacted the structure of libraries – physically as well as conceptually. A new generation of digital services platforms for libraries is emerging, designed to provide a more comprehensive approach to the management and access to all formats of library materials. Despite the modernization of libraries and their adaption to the digital age, the library still hold a critical role within community to serve its users, continuing to be beacons of information sharing, learning, and entertainment even amidst tight fiscal times.As one of the leading university in Indonesia, Bogor Agricultural University Library must find solutions to new challenges, overhaul many of their entrenched business processes, and foster systems that engage students.This study examined the information seeking behavior of the digital native and digital immigrant students of Bogor Agricultural University, in order to remind the library that there are some changes happened in its users and to recommend the new services should be taken by the library. The similarities and differences in seeking information of those two group students were discussed.